Pengaruh Musik J-Pop terhadap Mood dan Produktivitas Mahasiswa Saat Belajar - Ghaeril Juniawan Parel Hakim; Gandi Abetnego Simangunsong; Muhammad Rafi Rusafni; Muhammad Ilham Nurfajri; Humannisa Rubina Lestari (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
J-Pop music has become an important part of students’ lifestyles and plays a role in influencing their mood and learning productivity. This study employed a descriptive quantitative method by distributing an online questionnaire to 194 students who regularly listen to J-Pop while studying. Results showed that 69.8% of respondents felt their mood improved before studying when listening to this music, and 40.2% reported completing tasks more quickly. These findings indicate that J-Pop can serve as a positive stimulus to enhance motivation and focus during academic activities. However, its effects are subjective and highly dependent on individual preferences and study habits. Therefore, J-Pop has the potential to be part of an effective learning strategy if adapted to students’ personal characteristics and contexts. This study emphasizes the importance of considering psychological aspects when utilizing music as a learning aid to support students’ academic performance.